Random in Death: In Death # 58 - Robb, J. D; Ericksen, Susan ([United States] : Macmillan Audio, 2024)
Jenna's parents had finally given in, and there she was, at a New York club with her best friends, watching the legendary band Avenue A, carrying her demo in hopes of slipping it to the guitarist, Jake Kincade. Then, from the stage, Jake catches her eye, and smiles. It's the best night of her life. It's the last night of her life. Minutes later, Jake's in the alley getting some fresh air, and the girl from the dance floor comes stumbling out, sick and confused and deathly pale. He doesn't know that someone in the crowd has jabbed her with a needle, and when his girlfriend Nadine arrives, she knows the only thing to do is call her friend, Lieutenant Eve Dallas. After everyone on the scene is interviewed, lab results show a toxic mix of substances in the victim's body. Dallas searches for a pattern. What worries Dallas is, if Jenna wasn't targeted, if she was just the random, unlucky victim of a madman consumed by hatred, there are likely more deaths to come.
Compact disc.
01/23/2024
new cdbk 2024 winter.
Read by Susan Ericksen.
Keywords: Mystery; Suspense/Thriller.; Audiobooks; Fiction